Optimizing AI Technology in Assessing Islamic Financing Risks: A SWOT Analysis of Challenges and Opportunities from an Islamic Legal Perspective (Fiqh) - Wazin, Wazin; Siti Patimah; Aan Ansori; Wasehudin (Institut Agama Islam Negeri Curup, 2025)
This study aims to analyze the implementation of AI in Islamic financial risk assessment using a SWOT approach. The primary objective is to evaluate how AI can be integrated to enhance risk assessment effectiveness while ensuring compliance with Islamic legal principles (Fiqh), particularly the prohibition of Riba, the avoidance of Gharar, and the promotion of ethical transparency. A qualitative methodology with a descriptive analytical approach is employed in this research. Data sources include scholarly literature, regulatory policies, industry reports, and case studies related to AI adoption in Islamic finance. The analysis utilizes the IFAS and EFAS to assess internal and external factors influencing AI adoption. Additionally, an Islamic legal analysis is conducted to ensure that AI implementation aligns with Shariah principles. The findings reveal that AI has significant potential to enhance efficiency and innovation in Islamic finance. However, challenges such as infrastructure limitations and a lack of technological literacy pose obstacles to its implementation. From an external perspective, opportunities for financial inclusion and strategic technological partnerships are expanding, yet concerns regarding data security and regulatory uncertainties remain prevalent. From an Islamic legal standpoint, this study underscores the importance of developing an AI framework that adheres to Shariah principles. The adoption of AI in Islamic finance must follow a balanced approach by leveraging external opportunities, addressing internal challenges, and ensuring compliance with ethical and legal standards. This study offers strategic insights into AI integration within Islamic finance, contributing to its sustainability and global competitiveness.